2022
DOI: 10.3389/fimmu.2022.794006
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Cellular Immunological Interactions Associated With COVID-19 Infections

Abstract: To rapidly prognosticate and generate hypotheses on pathogenesis, leukocyte multi-cellularity was evaluated in SARS-CoV-2 infected patients treated in India or the United States (152 individuals, 384 temporal observations). Within hospital (<90-day) death or discharge were retrospectively predicted based on the admission complete blood cell counts (CBC). Two methods were applied: (i) a “reductionist” one, which analyzes each cell type separately, and (ii) a “non-reductionist” method, which estimates mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Other similar markers in both Wave 1 and Wave 2 included lymphopenia and elevations of procalcitonin, IL-6, d -dimer, and platelet count. Other studies have also indicated that absolute lymphopenia is not a predictor of outcomes by itself ( Verma et al, 2022 ). These indicators remain elevated in severe COVID-19 but do not differ between the waves ( Lopez-Castaneda et al, 2021 ;Malik et al, 2021 ).…”
Section: Discussionmentioning
confidence: 94%
“…Other similar markers in both Wave 1 and Wave 2 included lymphopenia and elevations of procalcitonin, IL-6, d -dimer, and platelet count. Other studies have also indicated that absolute lymphopenia is not a predictor of outcomes by itself ( Verma et al, 2022 ). These indicators remain elevated in severe COVID-19 but do not differ between the waves ( Lopez-Castaneda et al, 2021 ;Malik et al, 2021 ).…”
Section: Discussionmentioning
confidence: 94%
“…To measure personalized immune dynamics and to extract hidden patterns, the assessment of immunological complexity has been recommended [24][25][26]. To explore complexity, interactions involving two or more biological elements-such as lymphocytes and monocytes-may describe biological functions that influence outcomes [27]. Such complex functions change over time and may exhibit feedforward and feedback loops [9,28].…”
Section: Complex and Dynamic Interactions That Structure The Data And...mentioning
confidence: 99%
“…The previous considerations may influence the way immuno-competence is explored. In several clinical entities (e.g., COVID-19, sepsis, hantavirus), the early disease stage is not always associated with death [27,[37][38][39][40].…”
Section: Covid-19-related Dynamic and Personalized Immuno-competencementioning
confidence: 99%
See 1 more Smart Citation
“…Clinicians are overwhelmed by a complete change in viral symptoms every time there is a new strain in circulation [ 3 , 4 ]. Mathematical modeling has been helpful to only an extent [ 5 , 6 ], even with a much more extensive understanding of risk factors and prognosis [ 7 , 8 ]. Our group has shown the usefulness of heparin as a viral fusion inhibitor by targeting spike protein early on in the pandemic [ 9 ].…”
Section: Introductionmentioning
confidence: 99%